Frequency of Iron Deficiency Anemia Among Children a Multi-Center Study - Muhammad Younas Khan, Gule Lala, Kiramatullah, Sijad-Ur-Rehman, Javad Afridi (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Anaemia, marked by abnormally low levels of haemoglobin and often caused by an absence of iron, remains a severe public health problem in Pakistan. Studies have yet to be done on the prevalence of iron deficiency anaemia in children, making it essential to research the Khyber Pakhtunkhwa region to understand better how widespread this ailment is amongst the region’s pediatric populations. Objective: Determine the prevalence of iron deficiency anaemia in anaemic newborns between 6 and 66 months. Materials and Methods: This multi-center study was conducted between February 2022 and February 2023 at the Hayatabad Medical Complex pediatric department in Peshawar. The 180 enrolled children’s basic demographic information, including age, gender, and weight, were collected. Operational guidelines for automated analysis of iron deficiency anaemia collected venous whole blood samples. Results: The 180 kids ranged in age from 5 to 36 months for 65% (n=118) and 30 to 66 months for 35% (n=62), respectively. (10.44 SD) There were 30 months on average. Men comprised 40% (n=75) of the participants, while women comprised 65% (n=106). Additionally, 44% (n=80) and 58% (n=102) of the subjects were above 10 kg in weight. The average weight (05.20 SD) was 9.44 g/dl. Additionally, 76% (n=70) of the children had iron deficiency anaemia, compared to 23% (n=40) of those who did not. Conclusion: According to the study, 76% of kids aged 6 to 66 months had iron deficiency anaemia. Keywords: iron deficiency anaemia, children’s